2010
DOI: 10.1308/135576110791654793
|View full text |Cite
|
Sign up to set email alerts
|

The Prevalence of Dental, Facial and Head Injuries Sustained by Schoolboy Rugby Players. A Pilot Study

Abstract: Dental, orofacial and head injuries were commonly reported. Dental injuries were the most prevalent type of injury. All players used mouthguards regularly.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
24
0

Year Published

2013
2013
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 14 publications
(24 citation statements)
references
References 10 publications
0
24
0
Order By: Relevance
“…19 A study of English rugby union players found that 41% of players had experienced dental injuries, of which 37% were fractured teeth. 20,21 Another study found a high prevalence of soft tissue injuries, with 40% of Scottish rugby union players reporting injuries to the face or head requiring sutures. 4,20 Several published studies have investigated the prevalence of orofacial and dental trauma in participants of contact sports.…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations
“…19 A study of English rugby union players found that 41% of players had experienced dental injuries, of which 37% were fractured teeth. 20,21 Another study found a high prevalence of soft tissue injuries, with 40% of Scottish rugby union players reporting injuries to the face or head requiring sutures. 4,20 Several published studies have investigated the prevalence of orofacial and dental trauma in participants of contact sports.…”
Section: Introductionmentioning
confidence: 99%
“…20,21 Another study found a high prevalence of soft tissue injuries, with 40% of Scottish rugby union players reporting injuries to the face or head requiring sutures. 4,20 Several published studies have investigated the prevalence of orofacial and dental trauma in participants of contact sports. A high prevalence of dental injuries among schoolboy rugby union players in Australia and England has been reported.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…The questionnaire used in this study was similar to those used in previous studies [7,8]. As discussed previously the findings of such questionnaires must be interpreted with some caution [8] because the retrospective design means that data are subjective and accuracy is reliant on the memory of the subjects.…”
Section: Discussionmentioning
confidence: 90%
“…As discussed previously the findings of such questionnaires must be interpreted with some caution [8] because the retrospective design means that data are subjective and accuracy is reliant on the memory of the subjects. It is possible that minor injuries were forgotten or ignored for reporting purposes.…”
Section: Discussionmentioning
confidence: 99%